ПІДХОДИ ДО РОЗРАХУНКУ ЕКОНОМІЧНОГО КАПІТАЛУ БАНКІВСЬКОЇ СИСТЕМИ УКРАЇНИ - Шевчук, Антон Михайлович (Науковий журнал «Світ фінансів», 2017)
Шевчук А. М. Підходи до розрахунку економічного капіталу банківської системи України. Зазначено, що саме достатність капіталу визначає ступінь фінансової стійкості банку, тому є тим елементом ресурсної бази банку, який повинен покривати ризики, що виникають в його діяльності. Акцентовано увагу на тому, що низький рівень достатності капіталу банку призводить до небезпечних ризиків, що негативно позначається на його фінансовій стійкості. Здійснено порівняння підходів до розрахунку економічного капіталу банку. Шевчук А. М. Подходы к расчету экономического капитала банковской системы Украины. Указано, что именно достаточность капитала определяет степень финансовой устойчивости банка, являясь при этом элементом ресурсной базы банка, который должен покрывать риски, возникающие в процессе его деятельности. Акцентировано внимание на том, что низкий уровень достаточности капитала банка приводит к опасным рискам, негативно сказывающимся на его финансовой устойчивости. Проведено сравнение подходов к расчету экономического капитала банка. Shevchuk A. Approaches to the calculation of economic capital Ukraine banking system. Introduction. Indicated that it determines the degree of capital adequacy of financial stability of the bank, so there is the element of the resource base of the bank, which should cover the risks arising in its activities. Therefore, proposed on the one hand say that the greater range of operations conducted by the bank, the greater the volume of investments in it, the more losses it may incur and the more he should be the level of capital adequacy to ensure stability in the implementation of the relevant risks. The attention that the low level of capital adequacy of the bank leading to a dangerous increase risks a negative impact on its financial stability. The comparison of approaches to the calculation of economic capital. The purpose of the study is to determine the best approaches for calculating economic capital in the presence of risk in the banking system arising in connection with the stability of the economy and fluctuations in the banking system. Results. In the sense of economic capital calculation and the effectiveness of its many internal and external stakeholders with regard to banking institutions and organizations, such as the management of bank supervisory authorities, rating agencies and shareholders. Even before the transition to the stage of calculating economic capital of most Ukrainian banks to make a number of steps to ensure that the basic requirements for risk management. Conclusion. The regulation of capital adequacy of the bank must comply with two ends, as overstating this value and reducing its value affects the reliability of the bank